Malignant fibroma presenting as a hypoglycemia and coma in a 45‐year‐old male patient: A case report. Issue 11 (20th November 2022) - Hanif, Muhammad; Jaiswal, Vikash; Naz, Sidra; Patel, Nirmit; Pokhrel, Nishan Babu; Vadiyala, Mounika Reddy
Abstract: Solitary fibrous tumors (SFTs) are a rare group of spindle cell neoplasm of submesothelial origin with malignant potential and can present as hypoglycemia secondary to excess secretion of insulin‐like growth factor II (IGF‐II) from the tumor. Early diagnosis and treatment are very important in such cases to prevent hypoxic injury to the brain secondary to hypoglycemia. Here, we are presenting a case of a 45‐year‐old male patient, who presented with recurrent episodes of hypoglycemia spells, and later on, it was diagnosed that hypoglycemic spells were secondary to fibroma. Abstract : Solitary fibrous tumors (SFT) are quite rare tumors and can manifest hypoglycemia due to excess secretion of insulin‐like growth factor II (IGF II). Early diagnosis and treatment are very important in such cases, as prolonged and recurrent hypoglycemia can cause permanent changes in the brain.